Developing A Web-Based Application for Enhanced Transparency and Accountability of Financial Management in A School Cooperative Context - Novita Nurul Islami; Ravika Mutiara Savitrah; Wiwin Hartanto (CV. Sakura Digital Nusantara, 2026)
Purpose – Previous reports noted issues relating to transparency and accountability in the management of school cooperatives due to system errors, inefficiency, and limited real-time tracking with manual record-keeping of financial transactions. This study presents an application geared to tackle such challenges and lay the groundwork for further development in managing co-op financial needs. Design/methodology/approach – A Design and Development Research (DDR) approach was used along with the Software Development Life Cycle (SDLC) with the Waterfall model. Data collection involved observations, interviews, documentation review, and questionnaires. The system was developed through five phases: analysis, design, implementation, testing, and maintenance, all of which were carried out with the aid of this survey. The evaluation involved two information technology experts who were complemented by two accounting specialists. It included feasibility and user-driven usability assessments through a five-point Likert-scale instrument with five participants. Evaluations of transaction processes and financial reporting times before and after the application’s launch were used to track operational metrics over 30 transactions. Finding/Results – The findings suggest that the application is highly feasible in context and received very positive feedback throughout the limited testing. Feasibility of technology increased from 90% to 97.5%, while financial and accounting feasibility increased from 89.06% to 96.88%. Usefulness and satisfaction reached 98.18%. Operational appraisals also found time-related benefits in processing transactions and decent financial reporting. Originality/Value – This is an original study which optimizes accounting information system, real-time reporting, and inventory management a web-based solution. The researchers address only modest operational performance measures in to complement perception-based assessments in a small-scale environment